2009
DOI: 10.1021/tx900037u
|View full text |Cite
|
Sign up to set email alerts
|

The bis-Electrophile Diepoxybutane Cross-Links DNA to Human Histones but Does Not Result in Enhanced Mutagenesis in Recombinant Systems

Abstract: Abstract1,2-Dibromoethane and 1,3-butadiene are cancer suspects present in the environment and have been used widely in industry. The mutagenic properties of 1,2-dibromoethane and the 1,3-butadiene oxidation product diepoxybutane are thought to be related to the bis-electrophilic character of these chemicals. The discovery that overexpression of O 6 -alkylguanine alkyltransferase (AGT) enhances bis-electrophile-induced mutagenesis prompted a search for other proteins that may act by a similar mechanism. A huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…44 Although GAPDH and histone H3 with DEB form DNA-protein cross-links, the adducts are not mutagenic. 43,44 We previously reported a dramatic enhancement of base pair mutagenicity of DEB following GST expression in Salmonella typhimurium TA1535, 30,31 and subsequently a synthetic DEB-GSH conjugate was formed to be considerably more mutagenic than DEB or several other butadiene-derived epoxides in S. typhimurium TA1535. 32 …”
Section: Discussionmentioning
confidence: 99%
“…44 Although GAPDH and histone H3 with DEB form DNA-protein cross-links, the adducts are not mutagenic. 43,44 We previously reported a dramatic enhancement of base pair mutagenicity of DEB following GST expression in Salmonella typhimurium TA1535, 30,31 and subsequently a synthetic DEB-GSH conjugate was formed to be considerably more mutagenic than DEB or several other butadiene-derived epoxides in S. typhimurium TA1535. 32 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, four histidine and two tyrosine residues present in human CYP2E1 react with EB to form adducts (Boysen et al, 2007), although their impact on activity was not investigated. As a bifunctional electrophile, DEB can modify individual residues and form intra- and inter-protein crosslinks (Cho and Guengerich, 2012), as well as protein-DNA crosslinks (Loecken et al, 2009). In this study, we did not specifically investigate the covalent modification of rodent CYP2E1 enzymes by BD metabolites; however, we did not observe any irreversible inhibition/inactivation of CYP2E1 by EB and DEB that would suggest covalent binding.…”
Section: Discussionmentioning
confidence: 99%
“…16 Mass spectrometric analysis of tryptic peptides identified two cross-linking sites within the AGT protein: the catalytic alkyl acceptor site (Cys 145 ), and a neighboring active site residue (Cys 150 ). Loecken and colleagues have reported that DEB also forms DPCs involving GAPDH22 and histones H2b and H3 23. Like AGT, DPC formation by GAPDH involves a cysteine residue (Cys 246 ) 22.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylation of Cys 246 in vitro results in the inhibition of GAPDH activity 22. Similarly, DEB is capable of cross-linking the Cys 111 residue of histone H3 to DNA 23 . In vitro DPC formation by all three proteins required treatment with relatively high concentrations of DEB (20 mM for GAPDH and histone proteins and 15 mM for AGT) 16,22,23.…”
Section: Introductionmentioning
confidence: 99%